Effects of electric field and strain engineering on the electronic properties, band alignment and enhanced optical properties of ZnO/Janus ZrSSe heterostructures. Issue 17 (6th March 2020) - Vo, Dat D.; Vu, Tuan V.; Nguyen, Thi H. Tham; Hieu, Nguyen N.; Phuc, Huynh V.; Binh, Nguyen T. T.; Idrees, M.; Amin, B.; Nguyen, Chuong V.
Abstract : Here, in this work, we investigate the structural, electronic and optical features of ZnO/ZrSSe vdWHs for different stacking patterns of ZnO/SeZrS and ZnO/SZrSe by employing first-principles calculations. Abstract : The formation of van der Waals heterostructures (vdWHs) have recently emerged as promising structures to make a variety of novel nanoelectronic and optoelectronic devices. Here, in this work, we investigate the structural, electronic and optical features of ZnO/ZrSSe vdWHs for different stacking patterns of ZnO/SeZrS and ZnO/SZrSe by employing first-principles calculations. Binding energy and ab initio molecular dynamics calculations are also employed to confirm the structural and thermal stability of the ZnO/ZrSSe vdWHs for both models. We find that in both stacking models, the ZnO and ZrSSe layers are bonded via weak vdW forces, leading to easy exfoliation of the layers. More interestingly, both the ZnO/SeZrS and ZnO/SZrSe vdWHs posses type-II band alignment, making them promising candidates for the use of photovoltaic devices because the photogenerated electrons–holes are separated at the interface. The ZnO/ZrSSe vdWHs for both models possess high performance absorption in the visible and near-infrared regions, revealing their use for acquiring efficient photocatalysts. Moreover, the band gap values and band alignments of the ZnO/ZrSSe for both models can be adjusted by an electric field as well as vertical strains. There is a transformation from semiconductor to metal under a negative electric field and tensile vertical strain. These findings demonstrate that ZnO/ZrSSe vdWHs are a promising option for optoelectronic and nanoelectronic applications.